Strengthening regional capacity for climate services in Africa, Victoria Falls, Zimbabwe, 27 October 2015. - Mungai C; Atakos, Vivian; Hansen, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
CCAFS (through the International Livestock Research Institute and the International Research Institute for Climate and Society) and the Africa Climate Policy Center sponsored a workshop on ‘Strengthening Regional Capacity for Climate Services in Africa’, held on 27th October 2015 at Victoria Falls, Zimbabwe. The workshop, which was associated with and reported to the fifth conference on Climate Change and Development in Africa (CCDA-V), aimed to initiate a collaborative effort to strengthen capacity, through African regional institutions, to support smallholder farmers with relevant climate services. The workshop brought together 17 participants including scientists and technical experts to learn from and build on examples of good practice in farmer-focused climate information and advisory services, and to share elements of good practice in food security contingency planning.